PERAN KARANG TARUNA DALAM MENINGKATKAN KEPEDULIAN SOSIAL MASYARAKAT DI DESA POJOK KLITIH JOMBANG - Fifi Widyaloka; Diah Puji Nali (Jurnal Genta Mulia, 2025)
Currently many people especially the younger generation do not yet have a sense of social awareness, this is caused by the flow of globalization, so that people have an individualistic attitude and lack interaction. So that Karang Taruna has an important role in increasing social awareness in society and the younger generation. This study aims to (1) determine the social awareness of the community, (2) determine the form of Karang Taruna activities, and (3) determine the supporting factors and inhibiting factors of Karang Taruna in increasing social awareness. The method used by researchers in this study is a qualitative method. The results of this study are (1) the community's social awareness contains three elements, namely the community's empathy to help residents build houses, the community's mental attitude that is not easily influenced by the current of globalization, and the community's cooperative attitude in carrying out community service, (2) the form of Karang Taruna activities is community service, distributing social assistance to the underprivileged, and enlivening national holidays, and (3) Supporting factors from an internal perspective, namely Karang Taruna members are active in social activities and from an external perspective, namely participation and support from the community in social activities. Meanwhile, the inhibiting factors from the internal side are the lack of funds for Karang Taruna activities and from the external side, there are people who have less contribution to support Karang Taruna social activities.